2017
DOI: 10.1007/s10758-016-9296-6
|View full text |Cite
|
Sign up to set email alerts
|

Acquiring Critical Thinking and Decision-Making Skills: An Evaluation of a Serious Game Used by Undergraduate Dental Students in Dental Public Health

Abstract: Serious gaming claims to provide an interactive and motivational approach to learning; hence, it is being increasingly used in various disciplines, including dentistry. GRAPHIC (Games Research Applied to Public Health with Innovative Collaboration)-II, a serious game for dental public health, was used by dental undergraduates at King's College London, in the 2013-2014 academic year. The aim was to explore the use of GRAPHIC and student perspectives on the game. Students were divided into two groups with 79 stu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
34
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
3
3
1

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(34 citation statements)
references
References 17 publications
0
34
0
Order By: Relevance
“…Of the full-text articles reviewed, 11 were excluded because they were not SGs, 6 were not SGs in dentistry, 3 were secondary studies, and 1 paper was in French language. 3,[17][18][19][20][21][22][23][24][25][26][27][28][29][30][31][32][33][34][35][36] In addition, six studies were identified by 6,12,[37][38][39][40][41][42][43][44][45][46][47][48][49][50][51][52][53] corresponding to 19 studies, were included, because six studies were reported more than once. [54][55][56][57][58][59] Figure 1 shows the flow diagram of the selection process of our review.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Of the full-text articles reviewed, 11 were excluded because they were not SGs, 6 were not SGs in dentistry, 3 were secondary studies, and 1 paper was in French language. 3,[17][18][19][20][21][22][23][24][25][26][27][28][29][30][31][32][33][34][35][36] In addition, six studies were identified by 6,12,[37][38][39][40][41][42][43][44][45][46][47][48][49][50][51][52][53] corresponding to 19 studies, were included, because six studies were reported more than once. [54][55][56][57][58][59] Figure 1 shows the flow diagram of the selection process of our review.…”
Section: Resultsmentioning
confidence: 99%
“…About half of the SGs (n = 9) were developed in Brazil, 12,38,39,41,44,[47][48][49][50] three in the United Kingdom, 43,51,52 two in Taiwan, 37,45 and two in the United States. 6,53 A smaller number (n = 1) were developed in Germany, 46 Spain, 42 and South Africa.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In the period before GDPR introduction, eight studies or roughly 27% and in the period after nine studies or about 19% are concerned with Exergames when reporting on data protection. Examining the context of data protection phrases revealed that authors emphasised most the anonymisation of study artefacts such as transcripts [30], spreadsheets [38], blog-posts [35] or usage/interaction and activity profiles [24]. In both sub-collections, studies only sporadically reported on anonymisation of participants while also sometimes referring to "anonymising" when actually "pseudonymising" was performed [39].…”
Section: Data Protectionmentioning
confidence: 99%
“…students perceive themselves "in action" in a "reality of operation", even though the situation is simulated (Pastre, 2005, p. 3). Studies have demonstrated the advantage of implementing simulation and gaming into curriculum for student learning achievement, motivation, critical thinking, and problem solving (Gerber & Scott, 2011;Hwang & Chen, 2017;Sipiyaruk, Gallagher, Hatzipanagos, & Reynolds, 2017).…”
Section: Simulatorsmentioning
confidence: 99%